Heart failure with preserved ejection fraction in hypertension. (July 2016) - Teo, Loon Yee Louis; Chan, Laura Lihua; Lam, Carolyn Su Ping
Abstract : Purpose of review: Hypertension is the most prevalent risk factor in heart failure with preserved ejection fraction (HFpEF) and plays a key role in the disease. The continued lack of effective therapies to improve outcomes in HFpEF underscores the knowledge gaps regarding the pathophysiology of HFpEF. This review builds on fundamental concepts in pressure overload-induced left ventricular modeling, and summarizes recent knowledge gained regarding the mechanisms underlying the transition from hypertensive heart disease to HFpEF. Recent findings: The pathophysiology of hypertensive HFpEF extends beyond the development of left ventricular hypertrophy and diastolic dysfunction to myocardial contractile dysfunction, beyond left atrial structural dilatation to left atrial functional decline, beyond macrovascular stiffening to microvascular dysfunction, beyond central cardiac triggers to systemic endothelial inflammation, beyond fibrosis to titin changes, and beyond collagen deposition to qualitative changes in collagen. The central paradigm involves a systemic proinflammatory state triggering a downstream cascade of cardiac microvascular endothelial activation, oxidative stress, and abnormal myocardial cyclic guanosine monophosphate signaling, leading to microvascular rarefaction, chronic ischemia, fibrosis and progression to HFpEF. Summary: Recent advances have provided insights into the pathophysiology of HFpEF in hypertension. Such knowledge provides novel opportunities for therapeutic strategies in the treatment of hypertensive HFpEF.